2023
DOI: 10.3390/su151612632
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of Immigrant Students and Families: A Qualitative Study

María del Carmen Medina Podadera,
Antonio José González-Jimenez

Abstract: The perception that teachers have of cultural diversity is essential when it comes to the educational attention given to immigrant students. The objective is to determine how teachers perceive students’ cultural diversity and families’ commitment with the education of their children, and if this perception can influence teachers’ expectations regarding students and their families. This is qualitative research study based on hermeneutic phenomenology developed through semi-structured interviews, applied on an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Research has shown that cultural diversity establishes a misconception between parents' and teachers' needs. Ethnic stereotypes, either positive or negative (Podadera & González-Jimenez, 2023), can largely construct teachers' perception, for example Polish students are considered diligent and successful as they are receiving intense parental support (Shalloo, 2015). Parental attitudes towards HSC and education may be shaped by the different cultural norms or different schooling type (teaching strategies, assessments, homework) experienced in their homelands (Antony-Newman, 2019).…”
Section: Home-school Communicationmentioning
confidence: 99%
“…Research has shown that cultural diversity establishes a misconception between parents' and teachers' needs. Ethnic stereotypes, either positive or negative (Podadera & González-Jimenez, 2023), can largely construct teachers' perception, for example Polish students are considered diligent and successful as they are receiving intense parental support (Shalloo, 2015). Parental attitudes towards HSC and education may be shaped by the different cultural norms or different schooling type (teaching strategies, assessments, homework) experienced in their homelands (Antony-Newman, 2019).…”
Section: Home-school Communicationmentioning
confidence: 99%
“…Based on the analysis of the extant literature, the semi-structured interview protocol was prepared by including questions used in previous studies [34,100,125,126]. As already conducted by previous studies [127], the interview protocol was subjected to a preliminary test by asking the opinion of three employees to identify potential ambiguities in the questions. The questions were then reformulated to incorporate their suggestions and, according to other studies [128,129], the interview protocol was authenticated by a panel of four experts (two academics and two experts of qualitative research) that analyzed the questions and made some amendments that were incorporated in the final version of the interview protocol including 50 questions.…”
Section: Data Collectionmentioning
confidence: 99%
“…Giménez [48] considers that this positive interaction will encourage the participation of many individuals, uniting collaboration spaces to build the foundation of interculturalism through collective construction. Diversity is necessary to generate these principles of interculturality, reflecting constructs of coexistence and social cohesion [49]. Therefore, generating an intercultural project seeking to share a common life fosters new identities and ideas for community living [50,51].…”
Section: Introductionmentioning
confidence: 99%